A rapid gas chromatography quadrupole time-of-flight mass spectrometry method for the determination of polycyclic aromatic hydrocarbons and sulfur heterocycles in spilled crude oils. Issue 7 (2nd February 2022) - Filewood, Taylor; Kwok, Honoria; Brunswick, Pamela; Yan, Jeffrey; Ollinik, Jessica E.; Cote, Christopher; Kim, Marcus; van Aggelen, Graham; Helbing, Caren C.; Shang, Dayue
Abstract : Successful analysis of polycyclic aromatic sulfur heterocycles (PASH) and their alkylated forms (APASH) was completed for various crude oil samples. Abstract : Spilled crude oil samples contain various toxic compounds including polycyclic aromatic hydrocarbons (PAHs) as well as sulfur heterocycles (PASHs) and their related alkylated forms (APAHs and APASHs). In this study, a method was successfully developed employing a gas chromatography quadrupole time-of-flight (GC-QToF) mass spectrometer to quantitatively analyze both PAHs/APAHs and PASHs/APASHs in these samples. With GC-QToF, the monoisotopic mass of the compounds is distinguished, allowing the PASHs/APASHs to be extracted separately from the PAHs/APAHs in crude oil. A gas chromatography triple quadrupole (GC-MS/MS) mass spectrometer was also used to confirm that a GC-QToF is the preferred instrument for analyzing these compounds. With the use of PASH/APASH standards to determine response correction factors (RCFs) in relation to PAH standards, the developed method is capable of analyzing PAHs, APAHs, PASHs, and APASHs in a single injection. The use of RCFs allowed for the development of a practical polycyclic aromatic carbon (PAC) method for analyzing a total of 77 compounds of the 2 groups in crude oil. This newly developed method was applied to spilled crude oils, demonstrating its potential in toxicological study as well as oil spill forensic investigation.